Exploring The Genetic Implications of Endogamous Marriage In The Qur’an And Science - Hanifah, Yulianti; Nasir, Muhammad; Badarulzaman, Muhammad Hafiz; Faridatunnisa, Nor; Rofikoh, Linda (International Journal of Research, 2024)
With the advancement of time and scientific knowledge in the medical field, endogamous marriage now encompasses activities that may result in offspring with abnormalities or genetic diseases. This controversial issue has prompted the author to explore the theme of endogamous marriage according to the Qur'an based on Q.S an-Nisa' [4]: 23 and Q.S al-Ahzab [33]: 50 while incorporating a scientific perspective. This article adopts a qualitative approach based on a literature review with primary sources al-Qur’an, then correlates the Koran and science. The findings indicate that according to the Qur'an, endogamous marriage is deemed lawful, appropriate, and safe. From a scientific standpoint, endogamous marriage does not invariably entail the risk of producing offspring with defects or genetic diseases, as such outcomes may occur only if one or both parents carry recessive genes. Therefore, regardless of the type of marriage, the paramount consideration is the health status of the bride and groom. As a solution, the article suggests implementing mandatory pre-marital health screenings, especially for endogamous marriages. This approach aims to facilitate informed decisions in establishing harmonious households and ensuring the birth of healthy offspring.